Urgensi Pengembangan SDM (Sumber Daya Manusia) Lembaga Pendidikan Islam Era Digitalisasi - Zurtina; Jamilus (STAIN Bengkalis, 2024)
The aim of this research is to determine the importance of developing human resources in Islamic educational institutions with the development of digitalization which continues to grow and penetrate the world of education. This research takes a qualitative descriptive approach that emphasizes meaning, understanding, and finding solutions using literature reviews of scientific articles, books, papers, and other findings. Based on research findings, it is found that human resource development is very important in Islamic educational institutions in order to achieve success in the world and the hereafter with knowledge. The urgency for human resource development is to improve the quality of teaching, ease of learning resources, motivating students with innovative learning, ease of administration, sustainability and growth of Islamic educational institutions. With this urgency, Islamic educational institutions must also maintain the characteristics of their abilities, including: 1. Ability to educate, 2. Ability to conduct research, 3. Ability to build cooperation, 4. Ability to adapt, 5. Adhering to values and principles.